2019
DOI: 10.1002/joc.6389
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cloud base height in the North American Regional Reanalysis using ceilometer observations

Abstract: Future climate change predictions by global climate models or earth system models diverge significantly, most likely due to their different cloud responses to global warming. There is an uncertainty as to how the cloud frequency (or cloud fraction) and height will change, in turn, affecting the sign, and amount of cloud feedbacks. While satellite observations have been very useful in augmenting information on clouds, it is mostly related to cloud tops, and there is a lack of information on cloud base height (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…The NARR obtains CBH by taking the lowest level above the surface at which the cloud water/ice mixing ratio is greater than 10 −6 kg kg −1 . If no clouds are inferred by this method, the NARR algorithm checks for any convective clouds and returns their CBHs (An et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The NARR obtains CBH by taking the lowest level above the surface at which the cloud water/ice mixing ratio is greater than 10 −6 kg kg −1 . If no clouds are inferred by this method, the NARR algorithm checks for any convective clouds and returns their CBHs (An et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Dirmeyer et al (2013) illustrated SM‐precipitation feedbacks, whereas Halder et al (2015) outlined the need for both advanced LAFP and observations in simulating hydroclimatic variability over an extended region. Understanding of the ABL kinematics and thermodynamic features under extreme wet regime and associated LAFP is important since ABL features modulate numerous atmospheric processes, for example, CI, aerosol‐cloud microphysics, and turbulent mixing of aerosols and pollutants (e.g., An et al, 2019; Dirmeyer & Halder, 2016, 2017). Furthermore, the precipitation‐SM feedback process involves multiple nonlinear interactions among soil‐water storage, runoff, evapotranspiration, orographic features, vegetation cover, and precipitation types (Schubert et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the FAA requires the UAS to remain at least 152.4 m below the bases of clouds, and the UAS cannot fly in clouds for the flight restrictions being considered. An et al found that the NARR estimates the cloud base to be lower than the true cloud base in humid climates [19]. To account for this, our study filtered out a NARR product of combined low cloud and medium cloud percentage corresponding to clear skies when determining unsuccessful flights.…”
Section: Seasonal Climatologiesmentioning
confidence: 99%